Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5032/jae.2014.03017
|View full text |Cite
|
Sign up to set email alerts
|

Extension Youth Educators’ Technology Use in Youth Development Programming

Abstract: The purpose of this descriptive-correlational study was to determine the use of technology in youth programming by Extension youth development educators in Louisiana, Mississippi, and Tennessee. Data were collected via e-mail and a SurveyMonkey© questionnaire. Extension educators are using some technology in youth development programming. More than threefourths of Extension youth educators are using Facebook; however, less than one fourth of Extension youth educators are using Twitter which contradicts previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…These findings are similar to past research where Extension personnel had higher comfort and use in written communication than other communications activities, especially in the form of newsletters, and had lower comfort in mediarelated communication, such as TV and radio outreach, video editing, and graphic design (Erichsen, 2008;Hopkins, 2013;Telg et al, 2007). Amongst social media platforms, previous research has found Extension personnel have had higher comfort in Facebook compared to other platforms such as Twitter (McClure et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to past research where Extension personnel had higher comfort and use in written communication than other communications activities, especially in the form of newsletters, and had lower comfort in mediarelated communication, such as TV and radio outreach, video editing, and graphic design (Erichsen, 2008;Hopkins, 2013;Telg et al, 2007). Amongst social media platforms, previous research has found Extension personnel have had higher comfort in Facebook compared to other platforms such as Twitter (McClure et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Needs assessments are one of the most vital components of Cooperative Extension program development, as they can assist Cooperative Extension in standing out from competitors through an understanding of stakeholder needs and Cooperative Extension strengths and weaknesses (Garst & McCawley, 2015). While past research has considered perceptions of Cooperative Extension personnel and supervisors toward communication in the context of needs assessments, it has largely considered the two demographic groups separately and has not simultaneously compared traditional and newer technologies (Erichsen, 2008;Jernigan, Edgar, Miller, & Cox, 2015;McClure, Buquoi, Kotrlik, Machtmes, & Bunch, 2014;Meyers, Shaw, Irlbeck, Doerfert, & Abrams, 2015;O'Neill et al, 2011;Telg, Irani, Muegge, Kistler, & Place, 2007).…”
mentioning
confidence: 99%